Impact of community-based programs on anemia and stunting prevention: A multicenter randomized controlled trial - Darmawati, Darmawati; Dimiati, Herlina; Sufriani; Rizkia, Mira; Fitri, Aida; Kiftia, Mariatul; Halifah, Elka; Fithria; Ardhia, Dara (Acta Biomedica Atenei Parmensis, 2025)
Background and aim of the work: The urgency of the health problems of anemia and stunting has a long-term impact on the future of children, and the nation's intelligence, so appropriate intervention is required. This study aims to assess the effectiveness of Community-based interventions in preventing anemia and stunting.Research Design and Methods: The study used a Randomized Controlled Trial design. The population was pregnant women in Aceh Besar Regency; the sample was 86, but 6 people dropped out; therefore, the total was 80. Tools for data collection include knowledge, attitudes, and behavior questionnaires. This study measured the mother's weight, upper arm circumference, and Hemoglobin (Hb) levels, as well as the baby's weight and body length at the post-test.Results: The results showed that there were differences in the mean rank on the post-test knowledge (U= 587,500, P-value= 0.002), attitudes (U=363,000, P-value= 0.000), behavior (U= 469,500, P-value=0.001) which were significantly higher in the intervention group compared with the control group. However, the control and intervention groups did not differ in the mean ranking of Hb levels at the post-test (U= 688,000, P-value= 0.130). Control group newborns showed abnormality rates of 5.1% of body weight and 12.8% of body length.Conclusions: Good knowledge, attitudes, and behavior in the intervention group show that the community as an intervention partner has proven to be effective in preventing anemia and stunting in pregnant women, so routine education by nurses is needed to maintain the effectiveness of this intervention